KINERJA GURU SERTIFIKASI DALAM MENINGKATKAN PEMBELAJARAN PADA MADRASAH ALIYAH NEGERI (MAN) BEUREUNUEN KABUPATEN PIDIE - Erlina, Cut Zahri Harun, Nasir Usman (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2017)
Abstract: This study aims to examine the performance of post-certification schools teachers in their learning process, including: their ability, motivation, discipline, responsibility of school teachers in learning with existing supports and challenges. This study applies qualitative approach. Data is collected using interview, observation techniques, and documentation study. The subjects of this study are school’s principals, school’s representatives for curriculum affairs, school’s supervisor, and school’s teachers of Islamic State Senior High School of Beureunuen of Pidie Regency. The results of the study indicate that: (1) in general, the ability of the teachers in the learning process including the ability of planning and implementing learning administration has been optimal although there are still a number of teachers that consider learning administration is only complementary to the learning materials. The ability of teachers in evaluating the learning outcome, however, is still not optimal. The lack of learning evaluation ability was identified to be resulted from lack of continuous guidance from principals and supervisors, low ability of teachers in using Internet, and lack of opportunities in skill training, such as MGMP (Teacher Education Consensus Points). (2) The motivation of learning is also identified to be low in this study. The low motivation of teachers is identified to be affected by the factors such as lack of schools facilities and infrastructure. The findings also suggest that school’s principal can play a key role in improving the teachers’ motivation. (3) The discipline and responsibility of certified teachers is relatively high, which is supported by monitoring effort of stand-by teachers and finger-print scanner to record attendance at the Ministry of Religious Affair offices. (4) The results also suggest that supporting factors for teachers could be derived from the good school environment, while the challenging factors arise from the lack of facilities and infrastructure within the school.Keywords: Teacher Performance, Certification, and Learning Abstrak: Kinerja merupakan prestasi, hasil atau kemampuan yang dicapai dalam pelaksanaan tugas dan tanggung jawab. Guru sertifikasi hendaknya mempunyai kinerja yang optimal dalam melaksanakan proses pembelajaran untuk meningkatkan mutu pembelajaran. Sertifikasi adalah proses pemberian sertifikat kompetensi atau surat keterangan sebagai pengakuan terhadap kemampuan seseorang dalam melakukan suatu pekerjaan setelah lulus uji kompetensi. Tujuan penelitian ini adalah untuk mengetahui kinerja guru sertifikasi dalam pembelajaran, meliputi: kemampuan guru sertifikasi dalam pembelajaran, motivasi guru sertifikasi dalam pembelajaran, disiplin dan tanggung jawab guru sertifikasi dalam pembelajaran dan faktor pendukung serta penghambat guru sertifikasi. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Teknik pengumpulan data dilakukan melalui: wawancara, observasi, dan studi dokumentasi. Subjek penelitian adalah kepala madrasah, wakil bidang kurikulum, pengawas dan guru sertifikasi di MAN Beureunuen Kabupaten Pidie. Hasil penelitian menunjukkan bahwa: (1) kemampuan guru sertifikasi dalam pelaksanaan proses pembelajaran sudah optimal sebagaimana yang diharapkan. Meskipun masih ada sebagian guru yang menganggap administrasi pembelajaran hanya pelengkap bahan ajar semata. Sedangkan kemampuan guru sertifikasi dalam mengevaluasi hasil pembelajaran, belum memenuhi kriteria penilaian. Hal ini disebabkan karena guru sertifikasi kurang mendapat kesempatan untuk mengikuti pelatihan mengenai teknik evaluasi; (2) motivasi guru sertifikasi masih perlu ditingkatkan karena dipengaruhi oleh faktor sarana dan prasarana yang masih kurang memadai serta kepala madrasah merupakan motivator terbesar untuk meningkatkan motivasi guru; (3) Disiplin guru sertifikasi dan tanggung jawab sudah cukup tinggi ditambah lagi dengan pemberdayan guru piket beserta fingerprint dijajaran kantor Kementerian Agama; (4) faktor pendukung guru sertifikasi dalam pembelajaran berasal dari lingkungan sekolah yang nyaman, sedangkan faktor penghambat kurang tersedianya sarana, serta tidak tercukupi jam mengajar 24 jam perminggu.Kata Kunci: Kinerja Guru, Sertifikasi dan Pembelajaran